Strategic management and the economic efficiency of the enterprise - Binda, Jacek; Surówka, Marcin; Ambroży, Tadeusz; Kędra, Andrzej; Małodobry, Zbigniew (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The articles discusses the importance of strategic management in improving the economics efficiency of an enterprise . Strategic management combinations both business and economics aspects with the goal of maximizing a company’s efficiency and profitability . Although there is no clear definition , various approaches to strategic management include the process of analyzing the company’s environment, formulation strategy , implementation strategy , and monitoring and evaluating results . Additionally , etc indicates that strategic management is necessary for adapting to the changing environment, optimizing the use of resources and achieving the organization’s goals . The presented information also indicates that strategic management has three main levels incl the organization’s structure : corporate , strategic business units (SJG) and functional . Each of these levels plays a specific role within the company’s strategy . Ultimately , the articles emphasizes that strategic management is an integral element of the success of every company and is the foundation of its economics efficiency . A good business strategy allows a company to use resources effectively , adapt to a changing environment and achieve long-term goals .